2015
DOI: 10.1111/bjd.13958
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous toxicities associated with vemurafenib therapy in 107 patients withBRAFV600E mutation-positive metastatic melanoma, including recognition and management of rare presentations

Abstract: Vemurafenib appears to have a predictable and manageable AE profile. Proactive management can limit the impact of AEs on patients, allowing treatment to continue despite toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 26 publications
0
48
1
1
Order By: Relevance
“…b). High‐grade rash was reported in five trials and occurred in 396 out of 4001 total events; overall prevalence of high‐grade rash was 12.00% (95% CI 0.03–0.38) and Q = 495 ( P < 0.01; I 2 = 99%) (Fig. b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…b). High‐grade rash was reported in five trials and occurred in 396 out of 4001 total events; overall prevalence of high‐grade rash was 12.00% (95% CI 0.03–0.38) and Q = 495 ( P < 0.01; I 2 = 99%) (Fig. b).…”
Section: Resultsmentioning
confidence: 98%
“…Analysis of the prevalence of all‐grade cSCC associated with heterogeneity in patients with melanoma was performed for eight studies . Testing for interstudy heterogeneity gave significant results [ Q = 85.56; P < 0.01; I 2 = 91.8% (high heterogeneity was I 2 > 50%)].…”
Section: Resultsmentioning
confidence: 99%
“…3 According to a previous report, folliculitis was observed in 6-9% of patients who received vemurafenib, 4 while we postulate that the actual diagnosis may be acneiform eruption in some of these cases. In addition, BRAFi is known to induce other cutaneous adverse events related with keratinocyte proliferation, such as keratosis pilaris-like eruption, keratoacanthoma and squamous cell carcinoma.…”
mentioning
confidence: 73%
“…In addition, BRAFi is known to induce other cutaneous adverse events related with keratinocyte proliferation, such as keratosis pilaris-like eruption, keratoacanthoma and squamous cell carcinoma. 4 Recent studies have shown that paradoxical activation of mitogen-activated protein kinase (MAPK) pathway via CRAF, which is another component of RAF kinases, leads to increased keratinocyte proliferation. 5 Therefore, we hypothesize that BRAFi may induce the formation and increase of comedones especially in patients with the history of acne, who already have numerous comedones and microcomedones in their skin, through follicular keratinocyte proliferation by activation of the MAPK pathway.…”
mentioning
confidence: 99%
“…The treatment of patients with melanoma with the BRAF inhibitors vemurafenib or dabrafenib is associated with a multitude of cutaneous toxicities like UVA-dependent photosensitivity, follicular hyperkeratosis, papulopustular exanthema, erythema nodosum, palmoplantar hyperkeratosis, cysts, miliae and keratoacanthoma [4,13,[29][30][31][32][33][34][35][36]. Other side effects are neoplastic by nature, such as squamous cell and basal cell carcinoma or additional primary melanomas.…”
Section: Adverse Side Effects Of Braf Inhibitor Therapymentioning
confidence: 99%